Disorganising the unorganised: The 'Black Flood' and the Registered Metal Union responses, Part I, the 1960s, of South African 'development' - Sitas, A. (My University, 1981)
This paper arises out of a combination of two factors: firstly, it is out of a dissatisfaction with a reality presented to us of late by a number of articles and more voluminous affairs like books about the role of white-skinned people in the racial division of labour, and through that, South African society as a whole. Secondly, out of a feeling that the ever-recurrent debate about 'inter-racial solidarity' and the South African working classes has been spirited away by some theoretical formulations that like the best of imported machinery started producing a mass of realities that obfuscate rather than clarify real issues that the labour movement is facing at present. (2) Unlike Demag machinery though, the results of the former, produced a reality that in most cases does not exist. These two factors will increasingly become clear as the narrative unfords and need not detain us here. What needs to detain us here though is the plot of the ensuing argument. In the first two parts of this paper, the story of the shifts in the T.U.C.S.A. as concerns African unionisation and their affiliation, disaffiliation acrobatics that characterised much of the 1960s is told. It finally traces two divergent responses vis-a-vis the registered union movement. The one, spearheaded by what have been called 'craft-diluted' unions, the other by 'industrial unions'. The third part, concerns an exploration of the material complexities that characterise the 'craft-diluted' unions with a specific focus on the actual transformations in the metal industry in South Africa throughout the 1960s. The fourth part looks at the unions themselves and how they respond to their new-found reality, not at the point of leadership but rather at the actions and passivities of their respective ranks and files. The fifth part analyses what has been discussed so far in the light of the current debates about the class determination of the white wage-earning classes. The paper closes with the 1972 T.U.C.S.A. Conference and the clear polarisation/accommodatiorithat exists in strategy between registered unions: a year before Potgieter's Zulus took to the streets, their rags barely covering their bottoms but for completely different reasons than he gives or to use Nelson's bad metaphor, the year his Black-worker-Christ resurrects himself despite the washing of the hands of Pontius Pilate (read; colonial administrator; read: registered union movement).(3) The second part, or the second paper, at the moment in preparation, will be tracing the process to the present.
African Studies Seminar series. Paper presented May 1981
Keywords: Labor unions. South Africa